A numerical model of radio-frequency wall conditioning for steady-state stellarators - Kulyk, Yu.S.; Moiseenko, V.Е.; Wauters, T.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2018)
A new self-consistent model of the radio-frequency (RF) plasma production in stellarators in the ion-cyclotron
(IC) and electron-cyclotron (EC) frequency ranges is described in this work. This model will be used for RF and
ECRH start-up and for numerical analysis of the plasma discharge for the vacuum chamber wall conditioning in
stellarator type machines. The self-consistent model includes the system of the particle and energy balance equations
and the boundary problem for the Maxwell’s equations. A new feature of this model is account of molecular ions,
H₂⁺
and H₃⁺
, in the particle balance equations and possibility to model the ECRH breakdown. Представлено нову самоузгоджену модель високочастотного (ВЧ) створення плазми в стелараторах в
іонно-циклотронному (ІЦ) і електронно-циклотронному (ЕЦ) діапазонах частот. Ця модель буде
використовуватися для моделювання ВЧ- та ІЦ-створення плазми, а також для числового аналізу плазмового
розряду для очищення стінок вакуумної камери в установках стелараторного типу. Самоузгоджена модель
включає в себе систему рівнянь балансу частинок та енергії для електронів і крайову задачу для рівнянь
Максвелла. Новою особливістю моделі є врахування молекулярних іонів H₂⁺
і H₃⁺ у рівняннях балансу
частинок та можливість моделювати ІЦ-пробій. Представлена новая самосогласованная модель высокочастотного (ВЧ) создания плазмы в стеллараторах
в ионно-циклотронном (ИЦ) и электронно-циклотронном (ЭЦ) диапазонах частот. Эта модель будет
использоваться для ВЧ- и ИЦ-создания плазмы, а также для численного анализа плазменного разряда для
чистки стенок вакуумной камеры в установках стеллараторного типа. Самосогласованная модель включает в
себя систему уравнений баланса частиц и энергии для электронов и краевую задачу для уравнений
Максвелла. Новой особенностью модели является учет молекулярных ионов H₂⁺ и H₃⁺ в уравнениях баланса
частиц и возможность моделировать ИЦ-пробой.